Atmospheric oxidation of gaseous anthracene and phenanthrene initiated by OH radicals. (1st August 2020) - Zeng, Min; Liao, Zhihong; Wang, Liming
Abstract: Polycyclic aromatic hydrocarbons (PAHs) are ubiquitous environmental pollutants. In the atmosphere, PAHs are oxidized to oxygenated PAHs (OPAHs) and nitrated PAHs (NPAHs). However, the formation mechanism of OPAHs and NPAHs are unclear. Here we investigated the oxidation mechanism of anthracene (ANT) and phenanthrene (PHE) initiated by OH radical using quantum chemistry and chemical kinetic calculations. The oxidation starts by forming PAH-OH adducts which then react with O2 and NO2 in the atmosphere. Reactions of PAH-OH and O2 start mainly by reversible OO addition, forming PAH-OH-OO radicals, which then undergo backward decomposition to PAH-OH + OO, forward unimolecular isomerizations to OPAH products, and bimolecular reaction with NO. Effective rate of each route depends on the equilibrium constant of O2 addition and the rates of forward unimolecular and bimolecular reactions of PAH-OH-OO. We predicted that ANT-9-OH, PHE-4-OH, and PHE-1-OH would react slowly with O2 with effective rates at 298 K of ~18, ~50, and ~18 s −1, forming OPAH (2, 10-AQ for ANT); therefore, they would also react with atmospheric NO2, forming significant amounts of 9-NANT, 3-NPHE, and 2-NPHE, respectively. ANT-1-OH and PHE-10-OH would react rapidly with O2, forming OPAHs only. Predicted formation of 9-NANT and 3-NPHE agrees with field measurements in urban atmosphere where NPAHs are more likely formed from reactions of PAHs with OH and/or NO3 . On the other hand, observation of 9-NPHE might suggest a primary source of NPAHs such as biomass burning because 9-NPHE is highly unlikely formed in OH- and/or NO3 -initiated reaction of PHE. Graphical abstract: Image 1 Highlights: Reactivity of PAH-OH adduct towards O2 is isomer specific. All additions of O2 to PAH-OH adducts are reversible. Anthracene-9-OH could react with NO2 due to its slow effective reaction with O2 . Significant yield of 9-Nitroanthracene is expected. 9-NPHE arises likely from primary emissions since very low reaction formation.